The fickle nature of similarity change as a result of categorization. Issue 12 (December 2014) - Pothos, Emmanuel M.; Reppa, Irene
Several researchers have reported that learning a particular categorization leads to compatible changes in the similarity structure of the categorized stimuli. The purpose of this study is to examine whether different category structures may lead to greater or less corresponding similarity change. We created six category structures and examined changes in similarity within categories or between categories, as a result of categorization, in between-participant conditions. The best supported hypothesis was that the ease of learning a categorization affects change in within-categories similarity, so that greater (within-categories) similarity change was observed for category structures that were harder to learn.